An analysis of diets among patients with gastrointestinal disorders and a comparison of treatments, supplement use, and symptoms in Inflammatory Bowel Disease compared with other gastrointestinal disorders at Kenyatta National Hospital, Kenya - Onono, Rebecca Kivuli; Munene, Stella Makena; Thiauru, Lawrence Mugambi; Mapesa, Job Okoko (World Nutrition, 2025)
Background Inflammatory Bowel Disease (IBD) is a chronic gastrointestinal disorder (GD) in which both pharmacological treatment and dietary practices may influence symptom control, nutritional status, and disease progression. Dietary practices are integral to symptom management in IBD, yet context-specific data from sub‑Saharan Africa are limited. Objective This study aims to compare medication use, self-imposed dietary restrictions, and nutrition-related care between patients with IBD and those with other gastrointestinal disorders, to examine how these factors are associated with common symptoms. In addition, we describe patient-reported dietary intake patterns. Methods We conducted a hospital‑based cross‑sectional study at Kenyatta National Hospital (KNH). Adults (≥18 years) with confirmed IBD (n=40) and with other GD (n=79) were enrolled. Data were collected via structured questionnaires and records review. Analyses used descriptive statistics and χ²/Fisher’s exact tests (two‑sided, α=0.05). Results Use of core IBD pharmacotherapy was higher in IBD than GD (100% vs 75.3%; p<0.001). IBD patients more frequently reported therapeutic supplements (62.5% vs 39.2%; p=0.016) and preventive supplements (40.0% vs 15.2%; p=0.003). Restrictive therapeutic diets were common (47.5% IBD vs 34.2% GD; p=0.159). Diarrhea was more frequent in IBD (75.0% vs 50.6%; p=0.011); vomiting did not differ. Rates of documented nutritional deficiency ( 60%) and malnutrition ( 40%) were similar across groups. Diet intake patterns for both groups combined showed high reliance on staples and plant‑based proteins, with selective avoidance of animal fats and some animal proteins. Conclusions We conclude that IBD care at KNH features higher use of core medications, greater use of supplements, and higher diarrheal burden than for other GD. Patient‑directed dietary restriction and malnutrition were equally common in both groups. Routine nutrition screening and structured, individualized counselling, aligned with pharmacotherapy, may improve adequacy of dietary intakes while mitigating symptoms.